Standarisasi Instrumen Penilaian Hasil Belajar dengan Program Anates V4 Bagi Guru SMPN 17 Kota Jambi - Aulia Sanova; Abu Bakar; Afrida Afrida (Universitas Mathla'ul Anwar Banten, 2017)
Test question is a measuring tool that very important to determine the success of teaching and learning process. However, the main weaknesses of the teacher-made items are less structured construction. This weakness is usually because of the limited time teachers have in SMPN 17 Jambi for constructing the item test. If the analysis of these items is done manually, it will require a lot of time. Therefore, in the activities of community service will be used the program ANATES V4 for analyzing the test items. This program is used because it is easy and simple. The method used in this training are lectures, discussion-information/question and answer, demonstration and direct experiment. During the activity process, the participants are excited to practice the analysis of items directly and they are also already capable to carry out the analysis of the test form both multiple choice questions and essay. By analyzing the test, indirectly teachers can collect the test items or create “test item bank” that have validity and reliability.